Pengaruh Social Media Marketing dan Product Attractiveness terhadap Repurchase Intention melalui Brand Image pada Konsumen Batik Bakaran Pati - Dhimas Putra Na’imansyah; Hendar Hendar (Lembaga Yasin AlSys, 2026)
Competition in the fashion industry based on local culture requires business actors to optimize digital marketing strategies and product innovation in order to maintain consumer loyalty. This study aimed to analyze the effect of social media marketing and product attractiveness on consumers’ repurchase intention toward Batik Bakaran products in Pati Regency, with brand image as a mediating variable. A quantitative approach with an explanatory research method was employed, and data were collected through an online questionnaire administered to 150 respondents selected using purposive sampling. Data were analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the aid of SmartPLS 4.0 software. The results showed that social media marketing and product attractiveness have a positive and significant effect on brand image and repurchase intention. In addition, brand image was found to mediate the influence of social media marketing and product attractiveness on repurchase intention. These findings indicate that interactive social media content strategies and innovative visual product appeal play a crucial role in building a strong brand image and encouraging repurchase intention. The practical implications of this study underscore the importance of integrating digital marketing and strengthening product design for Batik Bakaran micro, small, and medium enterprises (MSMEs) to sustainably enhance consumer loyalty.